THE HISTORY OF COOPERATION WITH INTERNATIONAL ORGANIZATIONS IN FURTHER IMPROVING THE SOCIAL LIVING CONDITIONS OF THE POPULATION OF THE FERGHANA VALLEY (Scientific journal of the Fergana State University, 2023)
This article covers the socio-economic situation in the Fergana Valley regions in the early years of independence, reforms carried out by our government to improve the living standards of the population and cooperation with international organizations. As a result of the bans carried out, the wide-ranging relations of the UN with international organizations of different spheres and other European and eastern regions, considered one of the most influential international organizations of the world in increasing the social life of the population of Fergana Valley, were studied, as well as opinions were expressed about the prospects.